2021
DOI: 10.1021/acschemneuro.0c00737
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [18F]PS13 and Evaluation as a PET Radioligand for Cyclooxygenase-1 in Monkey

Abstract: Cyclooxygenase-1 (COX-1) and its isozyme COX-2 are key enzymes in the syntheses of prostanoids. Imaging of COX-1 and COX-2 selective radioligands with positron emission tomography (PET) may clarify how these enzymes are involved in inflammatory conditions and assist in the discovery of improved anti-inflammatory drugs. We have previously labeled the selective high-affinity COX-1 ligand, 1,5-bis­(4-methoxyphenyl)-3-(2,2,2-trifluoroethoxy)-1H-1,2,4-triazole (PS13), with carbon-11 (t 1/2 = 20.4 min). This radioli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Because of the short half‐life of carbon‐11 (20.4 min), 11 C‐labeled tracers cannot be distributed to remote imaging centers. After the promising results acquired with [ 11 C]PS13, the same group thus attempted to radiolabel PS13 with 18 F (half‐life 109.8 min) (Taddei et al., 2021). The resulting [ 18 F]PS13 was used to make two brain scans (at baseline and after pretreatment with unlabeled PS13) in two rhesus monkeys and a single whole‐body scan in one monkey.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the short half‐life of carbon‐11 (20.4 min), 11 C‐labeled tracers cannot be distributed to remote imaging centers. After the promising results acquired with [ 11 C]PS13, the same group thus attempted to radiolabel PS13 with 18 F (half‐life 109.8 min) (Taddei et al., 2021). The resulting [ 18 F]PS13 was used to make two brain scans (at baseline and after pretreatment with unlabeled PS13) in two rhesus monkeys and a single whole‐body scan in one monkey.…”
Section: Resultsmentioning
confidence: 99%
“…There has also been significant progress in the development of COX-2-targeting radioligands for imaging inflammation, cancer, and neurological disorders [54][55][56][57]. Over the last decades, a variety of radionuclide-based imaging agents have been developed by the incorporation of radioisotopes such as 11 C, 18 F, 99m Tc, 123 I, and 125 I into NSAIDs and related compounds [55,56,[58][59][60][61][62][63][64][65][66][67][68][69][70][71]. Selected examples of PET radioligands for COX-2 imaging are presented in Figure 3 Molecules 2022, 27, x FOR PEER REVIEW 3 of 20…”
Section: Introductionmentioning
confidence: 99%
“…There has also been significant progress in the development of COX-2-targeting radioligands for imaging inflammation, cancer, and neurological disorders [54][55][56][57]. Over the last decades, a variety of radionuclide-based imaging agents have been developed by the incorporation of radioisotopes such as 11 C, 18 F, 99m Tc, 123 I, and 125 I into NSAIDs and related compounds [55,56,[58][59][60][61][62][63][64][65][66][67][68][69][70][71]. Selected examples of PET radioligands for COX-2 imaging are presented in Figure 3 A major focus involves 18 F-labeled radioligands, due to their favourable half-life (t1/2 = 109.8 min), ease of production, the availability of a variety of radiofluorination methods, and better imaging characteristics of the short-lived positron emitter 18 F. This review article primarily covers 18 F-labeled radioligands reported in the last decade for targeting COX-2.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, [ 11 C]PS13 was evaluated in healthy humans, showing good test–retest reliability, and thus it would be interesting to investigate binding differences between healthy subjects and, for example, AD patients [ 129 ]. To provide a radiotracer with a longer half‐life, a [ 18 F]PS13 was developed, showing similar promising results in non‐human primates, however, optimization of the radiolabeling procedure is required to obtain [ 18 F]PS13 with sufficient molar activity [ 130 ]. [ 11 C]MC1 was evaluated in two healthy volunteers and two patients with rheumatoid arthritis as a proof of principle, and notably higher binding in inflamed joints was observed in patients versus controls [ 127 ].…”
Section: Introductionmentioning
confidence: 99%